Pengaruh berbagai formulasi pengencer dasar air kelapa terhadap kualitas semen cair sapi PO (Peranakan Ongole) selama simpan dingin (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2019)
Coconut water extender is the solution to the difficulty and high cots of procurement of diluents. The objective of this study was to examine the effect of various formulations of coconut water extender on quality of PO bull sperm during storage in 4-5 oC. This study was carried out at Animal Reproduction Laboratory of Faculty of Animal Husbandry Brawijaya University and Laboratory of Beef Cattle Research Center Grati Pasuruan on March to April, 2018. The study method used laboratory experimental. The experimental design was Factorial Randomized Completely Block Design and the data were analyzed by Analyze of Variance. There are four treatments in this study (P0 = CEP-3 + 20 % of yolk, P1 = Coconut Water + 20% of yolk, P2 = Coconut Water + 20% of yolk + 0,4% white egg + fructose 1 mg/ml, dan P3 = Coconut Water + 20% of yolk + 0,4% white egg + fructose 2 mg/ml) and ten replications of each treatment. There were significant differences in sperm motility between CEP-3 extender and coconut water-based with various formula extenders during chilled storage at 2-5 oC. But the treatment between coconut water-based formulas did not show a significant difference. Coconut water extenders are able to maintain sperm motility up to day 5 with values above 57%.